Optimal filtering - Anderson, Brian D. O. (Dover books on engineering., 2005)
This graduate-level text augments and extends studies of signal processing, particularly in regard to communication systems and digital filtering theory. Topics include filtering, linear systems, and estimation; the discrete-time Kalman filter; time-invariant filters; properties of Kalman filters; computational aspects; smoothing of discrete-time signals; and more. 24 figures. 1979 edition.